2018
DOI: 10.1188/18.cjon.326-332
|View full text |Cite
|
Sign up to set email alerts
|

Moral Distress: Using Mindfulness-Based Stress Reduction Interventions to Decrease Nurse Perceptions of Distress

Abstract: Moral distress was identified, with the finding that mindfulness interventions decreased nurse perceptions of distress. Healthcare providers offering a false sense of hope was the most frequently reported situation. Postintervention MDS-R survey results reflected a decrease in frequency of distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 20 publications
0
32
0
1
Order By: Relevance
“…24 Social work-led reflective debriefing, mindfulness-based stress reduction, moral empowerment programs, and supportive ethical climate are also associated with lower moral distress among critical care nurses. [25][26][27] Physician trainees have reported that being notified of and discussing patient deaths and participating in death rounds helped them cope with moral distress. 22 Austin et al propose an interdisciplinary approach to education of nurses and other clinicians that encourages better understanding of others' experiences of moral distress.…”
Section: Discussionmentioning
confidence: 99%
“…24 Social work-led reflective debriefing, mindfulness-based stress reduction, moral empowerment programs, and supportive ethical climate are also associated with lower moral distress among critical care nurses. [25][26][27] Physician trainees have reported that being notified of and discussing patient deaths and participating in death rounds helped them cope with moral distress. 22 Austin et al propose an interdisciplinary approach to education of nurses and other clinicians that encourages better understanding of others' experiences of moral distress.…”
Section: Discussionmentioning
confidence: 99%
“…Being able to make sense of the harshness of work may therefore be considered a protective factor to keep vocation alive and feel gratified, including in lack of (explicit) gratitude [58][59][60]. Personal balance and a solid philosophy of life are considered protective factors among nurses and medical doctors [61][62][63], including at the stage of education [64]. One interviewee reported how passion helped him to make sense of job challenges daily, to the extent of accepting and being aware of the physical consequences.…”
Section: External Pressure Vs Individual Balancementioning
confidence: 99%
“…This is confirmed by many contributions in literature. Primary care physicians receive fewer claims when their patients feel listened to [69]; nurses can accept more easily aggressive behaviors from patients when they are non-intentional [56], suspending the dichotomy between good and wrong, which is a factual example of the so-called "mindfulness" [62]; relatives can accept more easily the worsening of their beloved's health conditions when they are aware that it is not related to negligence from operators [70]; when the operators are aware of the patients' suffering, the latter may release part of their frustration [71]; sharing one's frustration with colleagues is a convenient release-valve [72,73].…”
Section: Sharing Daily Vs Accumulating Frustrationmentioning
confidence: 99%
“…Auch die schriftliche Reflexion eigener klinischer Erfahrungen kann zur Identifikation von MoS beitragen [26,29]. Achtsamkeitstraining hat darüber hinaus das Potenzial, sich positiv auf die Wahrnehmung von MoS auszuwirken [41].…”
Section: A) Hilfe Zur Selbsthilfeunclassified